Unveiling Strategic Mastery: Navigating the Nepalese Business Landscape for Competitive Advantage - Kathayat, Bhupal Bikram (Journal of Nepalese Management and Research, 2023)
This empirical investigation meticulously delves into the intricate facets of unveiling strategic mastery and its consequential impact on the configuration of the business landscape in Nepal, with a particular emphasis on the achievement of competitive advantage. The research embraced a positivist research philosophy and employed a descriptive research design, utilizing a survey method that incorporated structured questionnaires for the systematic collection of data. The sample size (324) was determined through convenience sampling across the seven provinces, and the Raosoft online statistical tool was utilized to calculate the necessary sample size. The study exclusively conducted inferential analysis, employing the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique to achieve its objectives. The investigation revealed that all the exogenous variables under consideration, namely strategic thinking, organizational agility, digital transformation, and risk and resilience, exhibited a conspicuous and statistically significant positive impact on the endogenous variable, i.e. competitive advantage. These findings, congruent with extant research, augment the study's credibility and furnish valuable insights for both academia and practitioners. The research contributes substantively to theoretical frameworks while concurrently supplying pragmatic guidance for decision-makers navigating complex business landscapes. Consequently, the study effectively bridges the theoretical-practical divide, imparting substantial benefits to the business organizations in Nepal.